Variabilidade de atributos físicos de um latossolo vermelho sob cultivo de cana-de-açúcar - Pereira Pellin, Douglas Martins; Montanari, Rafael [UNESP]; Lima, Elizeu de Souza [UNESP]; Lovera, Lenon Henrique [UNESP]; Correa, Adriany Rodrigues [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2015)
The goal of this paper was to select among the attributes surveyed soil, one with better representation to explain the variability of the technological components of sugar cane. The study was conducted at ETH Eldorado Plant in Rio Brilhante, MS, in the agricultural year 2011/2012, in a Oxisol, which was installed a geostatistical grid for data collection of soil and plant, with 80 sampling points, a 80 ha area. From the standpoint of linear and spatial TCH has been explained as a function of volumetric moisture. The volumetric moisture collected at a depth of 0.00 to 0.20 m, which had values between 0,24 to 0,270 m(3) m(-3), resulted in sites with the highest productivity of sugar cane per hectare from 64 to 70 t ha(-1). To aid future studies aimed at precision agriculture, which will use the same attributes as those of the future works, the values of ranges of spatial dependence to be used should be between 81 and 487 meters.

O objetivo desta pesquisa foi selecionar, entre os atributos físicos do solo, aquele com melhor representatividade para explicar a variabilidade dos componentes tecnológicos da cana-de-açúcar. O estudo foi realizado na Usina ETH Eldorado, em Rio Brilhante, MS, no ano agrícola 2011/2012, em um Latossolo Vermelho distrófico, onde foi instalada uma malha geoestatística para a coleta de dados do solo e planta, com 80 pontos amostrais em uma área de 80 ha. Do ponto de vista linear e espacial, o TCH foi explicado em função da umidade volumétrica, coletada na profundidade de 0,00-0,20 m, onde apresentou valores entre 0,240 a 0,270 m3 m-3, resultando em sítios com as mais elevadas produtividade de cana-de-açúcar por hectare entre 64 a 70 t ha-1. Visando auxiliar futuros trabalhos voltados à agricultura de precisão, os quais venham utilizar os mesmos atributos que os do presente trabalho, os valores de alcance da dependência espacial a serem empregados deverão estar compreendidos entre 81 e 487 metros.
Variability of physical properties of an oxisol under cultivation of sugar cane
Keywords: Saccharum spp.; Management and soil conservation; Spatial variability; Precision agriculture